The shapes of flow (Introduction to pure mathematics ; ;, 1987)
Summary: The Victoria Falls and the Whirlpool at La Rance Barrage are spectacular examples of flows. It turns out that for linear flows there are exactly 13 geometric varieties of flows that can occur, and that this number is tied up closely with eigenvectors of matrices.